Neurobiological mechanism of music improving gait disorder in patients with Parkinson’s disease: a mini review - Ling-Zhi Huang; Zhi Qi (Frontiers in Neurology)
Walking ability is essential for human survival and health. Its basic rhythm is mainly generated by the central pattern generator of the spinal cord. The rhythmic stimulation of music to the auditory center affects the cerebral cortex and other higher nerve centers, and acts on the central pattern generator. By means of rhythm entrainment, the central pattern generator can produce walking rhythm synchronized with music rhythm, control muscle tension, and then regulate human gait. Basal ganglia dysfunction is the main cause of abnormal gait in patients with Parkinson’s disease. Music therapy provides external rhythmic stimulation, recruits neural networks to bypass the basal ganglia and synchronizes gait with external rhythms in both time and space through auditory-motor neural networks, helping to promote the improvement of abnormal gait patterns in patients with Parkinson’s disease.